COMPUTATIONAL THINKING DALAM PEMBELAJARAN IPA: STUDI KASUS PADA MATERI RANTAI MAKANAN DI SEKOLAH DASAR - Aulia Rosiana; Anita kantini (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
ABSTRACT Elementary school students' understanding of food chain concepts is often limited to memorizing sequences of organisms without being accompanied by the ability to reason about relationships among ecosystem components in depth. This condition highlights the need for a learning approach that can foster systematic thinking skills while strengthening conceptual understanding. This study explored the implementation of the Computational Thinking approach in science learning on the topic of food chains among fifth-grade elementary school students. The study employed a descriptive method with a qualitative approach involving 30 students divided into six groups. The learning process was designed through activities focused on identifying patterns in various food chain examples, simplifying information into essential concepts, and constructing logical sequences of relationships among organisms. Data were collected through written tests, observations, questionnaires, interviews, and analysis of students’ worksheets. The findings revealed that students achieved 83% in pattern recognition, 67% in abstraction, and 100% in algorithmic thinking. In addition, 80% of the students obtained scores above the minimum mastery criterion on the food chain topic. Questionnaire and interview results indicated increased student engagement in discussions, greater interest in learning activities, and improved ability to explain relationships among organisms in a more systematic manner. These findings suggest that Computational Thinking not only supports the development of food chain concept mastery but also promotes more structured ways of thinking. The variation in achievement across the three foundations further indicates that abstraction requires more intensive instructional support than the other foundations in elementary science learning. ABSTRAK Pemahaman peserta didik sekolah dasar terhadap konsep rantai makanan sering kali masih terbatas pada kemampuan menghafal urutan organisme tanpa diikuti kemampuan menalar hubungan antarkomponen ekosistem secara mendalam. Kondisi tersebut menunjukkan perlunya pendekatan pembelajaran yang mampu mengembangkan keterampilan berpikir sistematis sekaligus memperkuat pemahaman konseptual. Penelitian ini mengkaji penerapan pendekatan Computational Thinking dalam pembelajaran IPA materi rantai makanan pada peserta didik kelas V sekolah dasar. Penelitian menggunakan metode deskriptif dengan pendekatan kualitatif yang melibatkan 30 peserta didik yang terbagi ke dalam enam kelompok. Proses pembelajaran dirancang melalui aktivitas identifikasi pola pada berbagai contoh rantai makanan, penyederhanaan informasi ke dalam konsep utama, serta penyusunan alur hubungan organisme secara logis. Data diperoleh melalui tes tertulis, observasi, angket, wawancara, dan analisis lembar kerja peserta didik. Temuan penelitian menunjukkan bahwa capaian kemampuan peserta didik pada fondasi pengenalan pola mencapai 83%, abstraksi 67%, dan algoritma 100%. Sebanyak 80% peserta didik juga memperoleh nilai di atas KKM pada materi yang dipelajari. Hasil angket dan wawancara memperlihatkan meningkatnya keterlibatan peserta didik dalam diskusi, ketertarikan terhadap pembelajaran, serta kemampuan menjelaskan hubungan antarorganisme secara lebih runtut. Temuan ini menunjukkan bahwa Computational Thinking tidak hanya membantu penguasaan konsep rantai makanan, tetapi juga membentuk cara berpikir yang lebih terstruktur. Perbedaan capaian pada setiap fondasi mengindikasikan bahwa kemampuan abstraksi memerlukan penguatan yang lebih intensif dibandingkan fondasi lainnya dalam pembelajaran IPA di sekolah dasar.